Diversity of bird in Timbanuh Hiking Track, Gunung Rinjani National Park, Lombok, Indonesia - Muhammadi, Robith Ridho; Zamroni, Yuliadi; Suana, I Wayan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Timbanuh Hiking Track is one of the hiking tracks in Gunung Rinjani National Park. This track has four types of potential habitats for birds. This research aims to map bird diversity and their distribution along the Timbanuh Hiking Track. Data collection uses the point count method. Observations were carried out eight times, with a repetition period of two weeks. Bird diversity was analyzed using the Shannon Wiener Diversity Index. Scatterplots are used to map the distribution of birds along hiking track. The results show that on the Timbanuh Hiking Track there are 46 species of birds belonging to 29 families, with a high species diversity index of 3.52. The distribution of bird species is closely related to the four types of habitats on the track. There are four species of birds that are protected based on Minister of Environment and Forestry Regulation Number P.106 of 2018, as well as two species with Near Threatened status according to IUCN. The high diversity of birds, the existence of protected bird species, and the threatened status of birds mean that conservation efforts need to be increased by developing bird habitats along hiking track.